2007
DOI: 10.1007/s10620-006-9453-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Silent Celiac Disease in Patients with Dyspepsia

Abstract: Celiac disease (CD) has become more common than in the past, although it frequently remains undetected for long periods of time. One reason for this is failure by health care professionals to recognize the variable clinical manifestations of CD and to perform the appropriate tests to make the diagnosis. Although dyspepsia may be part of a clinical spectrum in CD patients, there are scarce data about its prevalence in silent CD. We aimed to determine the prevalence of CD in otherwise healthy dyspeptic patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
1
15
1
1
Order By: Relevance
“…The correlations with IgA EmA and intestinal biopsy were 100% (Table 2). This result is similar to the findings of Riestra et al [33] in Spain (2.2% also in women); Ozaslan et al [21] in Turkey (1.5% in women). In another Brazilian region, Lima et al [34] reported 1.4% positivity in women.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The correlations with IgA EmA and intestinal biopsy were 100% (Table 2). This result is similar to the findings of Riestra et al [33] in Spain (2.2% also in women); Ozaslan et al [21] in Turkey (1.5% in women). In another Brazilian region, Lima et al [34] reported 1.4% positivity in women.…”
Section: Discussionsupporting
confidence: 92%
“…Point-of-care test in celiac disease be diagnosed at any age [1] . However, it frequently remains undetected for long periods of time, because of failure by health care professionals to recognize the disorder, probably due to the variable clinical presentation or failure to perform appropriate diagnostic tests [21] . In the present study, there was a young adult preponderance in all groups, indicating that it is important to exclude CD in the differential diagnosis of gastrointestinal complaints in this age group.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in other FGIDs including dyspepsia, the prevalence of CD has been reported to be higher than that in controls. 30, 31 However, because these studies were conducted in the secondary or referred population, unrecognized selection bias may account for these findings. Moreover, other studies including meta-analysis did not find significant associations between CD and dyspepsia.…”
Section: Discussionmentioning
confidence: 99%
“…Observaron la existencia de atrofia vellositaria en 8 (5,3%) pacientes: 2 de 48 (4,2%) pacientes con dispepsia, 4 de 52 (6,4%) pacientes con síntomas de reflujo gastroesofágico y 1 de 17 (5,8%) pacientes con náuseas y/o vómitos. Existen otros estudios que han evaluado la prevalencia de EC en pacientes con dispepsia, mediante la realización de serología seguida de EDA y biopsias de duodeno en los positivos 32,33,37 . Estos trabajos también han demostrado una mayor frecuencia de EC (1,5-5,9%) en comparación con la población general.…”
Section: Prevalencia De Enteropatía Sensible Al Gluten En Pacientes Cunclassified